The differences of the impact of a lipid and protein corona on the colloidal stability, toxicity, and degradation behavior of iron oxide nanoparticles - Rabel, Martin; Warncke, Paul; Thuermer, Maria; Gruettner, Cordula; Bergemann, Christian; Kurland, Heinz-Dieter; Mueller, Frank A.; Koeberle, Andreas; Fischer, Dagmar (Nanoscale, 2021)
Aim: In this study, the influence of a serum albumin (SA) and human plasma (HP) derived protein- and lipid molecule corona on the toxicity and biodegradability of different iron oxide nanoparticles (IONP) was investigated. Methods: IONP were synthesized and physicochemically characterized regarding size, charge, and colloidal stability. The adsorbed proteins were quantified and separated by gel electrophoresis. Adsorbed lipids were profiled by ultraperformance liquid chromatography-ESI-tandem mass spectrometry. The biocompatibility was investigated using isolated erythrocytes and a shell-less hen's egg model. The biodegradability was assessed by iron release studies in artificial body fluids. Results: The adsorption patterns of proteins and lipids varied depending on the surface characteristics of the IONP like charge and hydrophobicity. The biomolecule corona modified IONP displayed favorable colloidal stability and toxicological profile compared to IONP without biomolecule coronas, reducing erythrocyte aggregation and hemolysis in vitro as well as the corresponding effects ex ovo/in vivo. The coronas decreased the degradation speed of all tested IONP compared to bare particles, but, whereas all IONP degraded at the same rate for the SA corona, substantial differences were evident for IONP with HP-derived corona depending on the lipid adsorption profile. Conclusion: In this study the impact of the proteins and lipids in the biomolecule corona on the entire IONP application cycle from the injection process to the degradation was demonstrated.
CRIS-Team WoS Importer:2021-05-28